Assessment of CO2 and O2 spatial variability in an indigenous aquaculture system for restoration impacts - Evan Lechner; Yoshimi M. Rii; Kathleen Ruttenberg; Keli‘iahonui Kotubetey; Christopher L. Sabine (Frontiers in Marine Science, 2022)
Spatial variability in carbon dioxide (CO 2 ) and oxygen (O 2 ) was assessed within an Indigenous Hawaiian fishpond undergoing active ecosystem restoration. The brackish, tidal fishpond is located within Kāne‘ohe Bay, Hawai‘i. Following a year of monthly discrete sampling, a significant shift in DIC and percent O 2 saturation was observed along the North-South axis within the pond. The south end of the pond was higher in DIC (+35 μmol·kg⁻¹) and lower in percent O 2 saturation (-19%) than the north end, which exhibited values similar to those observed in water entering the fishpond from the bay. Water quality parameters and inequal proximity to water flux sites suggested that a difference in residence time may exist along the north-south axis. In addition, ΔTA/ΔDIC relationships revealed a respiration signal in south end of the pond, which was enhanced at depth. While physical processes strongly affect CO 2 and O 2 across various temporal scales, spatial patterns in biological processes may also affect variability within the fishpond. These findings demonstrate that changes in water chemistry within the fishpond are the result of ecosystem restoration efforts. In turn, future management decisions at the fishpond will play an important role in preserving its viability as a healthy habitat for the intended marine species.